Nutritional value, bacterial count and sensory attribute of little tuna (Euthynnus affinis) floss incorporated with banana blossom - Hartati Kartikaningsih; Yahya Yahya; Trihartita Yuniar; Abdul Aziz Jaziri; Wahidu Zzaman; Rovina Kobun; Nurul Huda (HACCP Consulting, 2021)
The study aimed to evaluate the addition of banana blossom (12.5, 25, 37.5, and 50% w/w) on nutritional quality, histamine content, bacterial count, and sensory characteristic in the fish floss prepared from little tuna (Euthynnus affinis). The crude protein content, essential amino acids, lipid, and polyunsaturated fatty acids (PUFA) steadily decreased (p <0.05), while the crude fibre, carbohydrate, and ash components of the tuna floss, increased significantly (p <0.05) with increasing levels of banana blossom. The contents of protein, fat, ash, fibre, carbohydrate, and moisture ranged 28.13 – 30.27%, 14.79 – 18.02%, 4.45 – 5.68%, 2.6 – 3.5%, 27.81 – 31.01, and 16.45 – 17.39%, respectively, and most of them met the Indonesian National Standard. For essential and non-essential amino acids, the level varied about 102.82 mg.g-1 to 206.76 mg.g-1 and 79.71 mg.g-1 to 138.76 mg.g-1, respectively in the treated tuna flosses. Moreover, ranging 13.72 – 16.29% of PUFA was found in all treated flosses. The most significant effect was found in the histamine levels of the tuna flosses, especially in the 50% added floss sample. Moreover, bacterial counts and heavy metals content were lower than the maximum limits regulated by the Indonesian National Standard. For sensory evaluation, the banana blossom-added samples significantly increased (p >0.05) the acceptability score for all attributes assessed. Taken together, the tuna floss added with 37.5% of banana blossom may be potentially developed as a low-histamine tuna-based product with high fibre and EPA+DHA, as well as highly acceptable for consumers.